Space, power and sexuality: transgressive and transformative possibilities at the interstices of spatial boundaries. Issue 3 (4th March 2018) - Peyrefitte, Magali; Sanders-McDonagh, Erin
Abstract: The themed section consists of articles that explore the relationship between power and space in relation to gender and sexuality by looking at processes of transgression, subversion or expansion of normative spatial practices and narratives. Using a theoretical framework that draws out power and space within a more specific context of feminist and queer literature, the articles explore the possibility to transgress, subvert or expand norms at the interstices of spatial boundaries beyond traditional binaries and hierarchies. Collectively, the articles call for a continued theoretical and methodological focus into the importance of looking at everyday sites of struggles and resistance in the crevasses, the liminal zones of space. The transgression of spatialized norms of sexuality and gender present a transformative potential that should be recognized for its political significance but, we argue, with caution as heteronormative and heteropatriarchal norms too often remain de rigueur in a neoliberal context.